NOMINATIVE EXPRESSIVE SENTENCES IN THE STRUCTURE OF THE TEXT - Korzhak, Z. Z. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
This article is about positional possibilities of nominative expressive sentences in the structure of the text. The medial position make its usage simultaneously autosemantic and text. The medial position make its usage simultaneously autosemantic and integrated. Synthesizing and forming the constituations of different systematic content such sentences have the characteristics approaching them to maxims. Cutting the narration short and at the same time sending the static of description, sentences of this type form connotations such as “passivity”, “contemplation” and so on. This article is also about nominative sentences used at the end of more or less extended text. Presupposition that comes forward as the main source of adequate perception of sense of the eventual nominative suggestions is focus in a previous context and fixed it’s of the retrospective connections. These sentences are entered in text as the conclusion, effective generalization of that about what is already said. Owing to their tendency towards laconic brevity, conciseness and integrity of syntactical constructions the postpositive nominative sentences reveal the various extent of their expressivity.